2011
DOI: 10.1007/s10531-011-0073-5
|View full text |Cite
|
Sign up to set email alerts
|

The value of fruit security for the conservation of a neotropical frugivore in human-dominated landscapes

Abstract: Understanding which habitat elements are critical for species' persistence in the human-dominated landscape is a fundamental challenge of conservation biology. In human-altered lands fruit can be less reliably available compared to intact forest, but it is unclear whether this affects generalist frugivores, the primary providers of the important ecosystem service of seed dispersal. Does the habitat element of fruit constancy influence the persistence of these species in human-altered lands? Radio-telemetry, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…However, Neotropical birds are an enormously diverse group, so secondary forest colonization rates are likely to vary greatly among different bird species and between the assemblages in different forest strata (Laurance et al., ). In contrast to understory species, many canopy species are able to disperse across open areas (Burney & Brumfield, ; Graham, ; Graham & Blake, ; Peters & Nibbelink, ) and hence reassembly might be faster in the canopy compared to the understory in isolated forests. Alternatively, reassembly in the canopy may be limited because many canopy species require an advanced level of structural complexity or resource availability before they can inhabit an area (Nadkarni, ; Nadkarni & Matelson, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, Neotropical birds are an enormously diverse group, so secondary forest colonization rates are likely to vary greatly among different bird species and between the assemblages in different forest strata (Laurance et al., ). In contrast to understory species, many canopy species are able to disperse across open areas (Burney & Brumfield, ; Graham, ; Graham & Blake, ; Peters & Nibbelink, ) and hence reassembly might be faster in the canopy compared to the understory in isolated forests. Alternatively, reassembly in the canopy may be limited because many canopy species require an advanced level of structural complexity or resource availability before they can inhabit an area (Nadkarni, ; Nadkarni & Matelson, ).…”
Section: Introductionmentioning
confidence: 99%
“…). We used MCP instead of kernel estimators because the former performs better at low sample sizes, such as in the case of our daily ranges (Sharp ; Peters & Nibbelink ). Range area calculations were performed in the program R (version 2.11.1; R Development Core Team ) using package ‘Adehabitat’ (Calenge ).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have shown that sampling regime might be even more important than sample size in affecting range area estimates (B€ orger et al 2006). We used MCP instead of kernel estimators because the former performs better at low sample sizes, such as in the case of our daily ranges (Sharp 2009;Peters & Nibbelink 2011). Range area calculations were performed in the program R (version 2.11.1; R Development Core Team 2010) using package 'Adehabitat' (Calenge 2006).…”
Section: S T a T I S T I C A L M O D E L Smentioning
confidence: 99%
“…Several studies have reviewed the impacts of coffee intensification on bird abundance, richness, and community composition (e.g., Greenberg et al 1997a,b;Johnson 2000;Roberts et al 2000;Perfecto et al 2003;Komar 2006;Philpott et al 2008). Many have documented changes in resource use, foraging behavior, and roost selection based on differences in availability and stability of fruit and floral resources (Carlo et al 2004, Peters & Nibbelink 2011, Bakermans et al 2012, epiphytes (Cruz-Angón et al 2008), and distance to forest fragments (Luck & Daily 2003, Jirinec et al 2011). Coffee farms have been used as laboratories for understanding how sex and age influence bird foraging behavior ( Jones et al 2000) and how foraging strata influence infestation of birds by mite parasites (Dietsch 2008).…”
Section: Competition and Foraging In Bird Assemblagesmentioning
confidence: 99%